(untitled) (SCIENCE TIME JOURNAL, 2026)
This article develops and substantiates an innovative visual-learning framework for teaching physics in specialized military schools during digital transformation. The study follows a theoretical-analytical and design-based case-study approach grounded in national policy documents on educational digitalization, research on interactive simulations, computational modeling, multimedia learning, cognitive load, and LMS-based analytics. The central argument is that, in a military-academic context, physics should be taught not as a static body of formulas but as a model-based language for describing motion, constraints, uncertainty, and decision-making. The paper proposes three interrelated visual-learning models: (1) dynamic simulation-based conceptualization, (2) multi-representational computational modeling, and (3) LMS-embedded interactive visual assessment. Mechanics and introductory ballistic trajectory tasks are used as demonstrative cases because they require synchronized qualitative reasoning, mathematical formalization, and algorithmic verification. The analysis shows that visual models become pedagogically productive when they reduce invisible processes to inspectable structures, support guided inquiry, and provide immediate feedback through dashboards and interactive content. The resulting framework is suitable for Temurbek specialized military schools and similar institutions seeking to align subject teaching with engineering reasoning, digital didactics, and evidence-based instructional design.